Hybrid Learning, Learning Motivation, and Academic Performance: Empirical Evidence from Economics and Business Students in Indonesia - Welimas Kristina Parinsi; Anugrah Dwi Lestari Musa; Kartika Septiary Pratiwi Musa (Abadi Institute, 2026)
This study investigates the influence of hybrid learning and learning motivation on students’ academic performance at the Faculty of Economics and Business, Universitas Negeri Makassar. Using a quantitative associative design, data were collected from 60 students selected through purposive sampling, all of whom had experienced hybrid learning. A structured questionnaire measured perceptions of hybrid learning, learning motivation, and academic performance. Descriptive statistics, multiple linear regression, t-tests, and F-tests were conducted using SPSS and Microsoft Excel. The results show that both hybrid learning (B = 0.634; Sig. = 0.003) and learning motivation (B = 0.679; Sig. = 0.000) significantly and positively influence academic performance. The model also demonstrates strong overall significance (F = 80.793; Sig. = 0.000), confirming that the two independent variables jointly predict academic outcomes. Hybrid learning enhances flexibility, interaction quality, and technological accessibility, which in turn strengthens students’ motivation and engagement. Motivated students exhibit stronger initiative, better time management, and more consistent participation, contributing to improved academic achievement. These findings highlight hybrid learning as a strategic instructional approach that supports motivation-driven academic performance. The study recommends that higher education institutions integrate hybrid learning frameworks with motivation-enhancing strategies to strengthen student outcomes. Future research should broaden the sample and involve multiple institutions to enhance generalizability.